The Role of THBS4 in Chronic Kidney Disease Fibrosis: From Clinical Observations to Molecular Mechanisms - Xu Yan; Kun Zhao; Ye Yao; Lihui Wang; Wei Shan; Yan Zhang (Frontiers in Bioscience-Landmark)
Background: Chronic kidney disease (CKD), driven by progressive renal fibrosis, lacks effective therapeutic targets. This study investigates thrombospondin-4 (THBS4) as a novel mediator of CKD-related fibrosis and explores its mechanistic basis. Methods: This study collected 100 patients diagnosed with chronic kidney disease and 30 healthy individuals. Enzyme-linked immunosorbent assay (ELISA) analysis was conducted to assess the expression of THBS4 in CKD patients. Mouse unilateral ureteral obstruction (UUO) renal fibrosis model and Human Kidney-2 (HK2) cell fibrosis model were constructed to analyze the expression changes of THBS4 in renal fibrosis. To examine the effects of inhibiting THBS4 expression on the process of renal fibrosis, these two models were analyzed using Sirius red staining, Masson staining, immunohistochemistry, real-time quantitative PCR (qPCR) and western blot methods. Results: The expression of THBS4 in the serum of CKD patients was found to be significantly higher (p < 0.05), and its concentration showed a negative correlation with the eGFR levels (r = –0.77, p < 0.05) and an increase corresponding to the progression of CKD stages (p < 0.05). THBS4 expression was dramatically increased in UUO-treated mouse kidneys as well as in TGF-β1-stimulated HK2 cells (p < 0.05). In vitro, the expression of renal fibrosis-associated proteins was also significantly reduced after interfering with THBS4 expression (p < 0.05). UUO-induced renal fibrosis and related protein expression were suppressed in THBS4 knockdown mice when compared to control mice (p < 0.05). The levels of p-AKT and p-PI3K exhibited a significant rise in conjunction with the onset of renal fibrosis (p < 0.05). The expression of p-AKT as well as p-PI3K showed a significant reduction upon inhibition of THBS4 expression (p < 0.05). Insulin-like growth factor 1 (IGF-1) treatment reversed these effects. Conclusion: THBS4 was significantly overexpressed in CKD patients. By suppressing the expression of proteins associated with renal fibrosis and inhibiting the activation of the PI3K/AKT pathway, THBS4 has the potential to mitigate renal fibrosis.